The problem of musical experience and intonation theory of music - Aida M. Ailamazyan; Nina L. Savchenko (Теоретическая и экспериментальная психология)
Background. Despite the growing interest in the field of music psychology, the problem of musical experience remains the least developed. Psychological studies take into account the subjective side of musical experience, but usually leave aside the correlation between the characteristics of perception and the actual musical meanings. The works of musicologists, in their turn, reflect the relationship between experience and the structural features of the form of a musical work. Objective. The study has two aims: 1) to provide a theoretical and methodological analysis of ideas about musical experience in the psychological and musicological traditions, 2) to consider the intonation theory of music and show its relevance for the psychological studies of musical experience. Methods. A comparative analysis of the concepts of musical perception and experience in the intonational music theory and psychological theories. Results. Presented analysis allowed to formulate the main features of musical experience, identified on the basis of musicological works. The perception of a musical work is based on the musical form as well as intonation, which allows to conclude that musical experience, on the one hand, is procedural and, on the other hand, is characterized by integrity determined by the meaning of the musical work behind it. Conclusions. The reference to the description of musical experience in the works of musicologists developing the intonation theory of music allows to approach a theoretical comprehension of musical experience as an activity of understanding the meanings of a musical work based on the intonation hearing and perception of intonation development in music. The study highlighted the grounds for characterizing musical experience: fragmentarity — integrity, subjectivity — reflection of the meanings of the musical work, uncertainty of emotional response — differentiated emotional experience, static character — perception of dynamics in music.